Evaluation of Reactive Powder Concrete Strength using Various Curing Methods - Albakry, Baraa A.; Abbas, Zena K. (Engineering, Technology & Applied Science Research, 2025)
This study examines the strength development of Reactive Powder Concrete (R-P-C) under various curing methods. The R-P-C mixture was prepared using a ratio of 1:0.25:1.11 by weight of high-quality ordinary cement, Silica Fume (S-F), and fine Sand (S), along with 2% by concrete volume of micro steel fibers. In addition to Normal Curing (R-N) utilized as a control approach, three alternative curing methods were evaluated: Autogenous + Normal Curing (R-AN), Steam + Normal Curing (R-S), and coating with a Water (W)-based liquid curing compound (R-C). The results indicated that R-S significantly enhanced the compressive strength of R-P-C as the curing duration increased from 1 to 3 days. The strength improvements at 7, 28, and 90 days were measured at 13.99%, 15.97%, and 16.47% for 1 day of R-S; 15.42%, 17.44%, and 18.48% for 2 days; and 17.52%, 18.49%, and 20.04% for 3 days. This method accelerated chemical reactions within the cement matrix, having promoted stronger bonds and higher early-age strength, making it the most effective technique for maximizing the strength gain. R-AN for 2 days, followed by 26 days of W immersion, also proved beneficial, having increased compressive strength by 10.85%, 11.05%, and 12.2% at 7, 28, and 90 days, respectively. This method effectively retained moisture, having facilitated optimal chemical reactions and steady strength development. Similarly, (R-C) improved compressive strength by 12.55%, 12.71%, and 13.82%, having minimized evaporation and maintained internal moisture. Furthermore, improvements in compressive strength were accompanied by proportional increases in flexural and splitting tensile strengths across all curing methods.